TEHERAN - Kongsgaard, Leif Tøfting (Tidsskriftet Antropologi, 2003)
In this article it is argued that Tehran itself as well as the Iranians’ conception of Tehran is changing. The size of Tehran, the capital of Iran, has within a few decades risen explosively from no more than 300.000 inhabitants in the 1930s to more than 9 million people today. At the same time the city has experienced a radical demographic divide between the lower, warmer, poorer and more traditional South and the richer, more modern North close to the cooler mountains. The conception of Tehran today is that of “a modern part” of Iran; i.e. North Tehran. While everybody agrees that Tehran is modern, the significance of this modernity is vehemently debated. The technological and financial aspect of Tehran’s modernity is unanimously seen as a positive feature, whereas the individualistic aspect of this modernity to some Iranians is seen as a moral threat to society, while others see it as a liberalising and positive force in society. In other words Tehran has become the battlefield of morality where “true Islam” meets “modern corruption”, “true Iranianism” meets “Western decadence” etc. And nowhere is this seen more explicitly than in the parks of Tehran. The urban parks have within the last decade developed into semi-private spaces partly free of government control, neighbours’ gossip and family restrictions. The culture of the private space (the home) has thus been moved into the public space, and at the same time this transformation causes the emergence of the modern, secularised urban individual, which to some extent demands separation of religion and state. This urban individual can no longer be controlled by the local priest and cannot be restricted from receiving news and viewpoints from outside of the national state-controlled media. Tehran has in this way become a physical and symbolical battlefield, where the dialectical and often contradicting moral consequences of modernity are being negotiated, restricted and craved.